Analisis Keuangan Terhadap Penyaluran Dana Tepat Guna Dalam Sebuah Kredit - Saputra, Andrian (IJMA (Indonesian Journal of Management and Accounting), 2023)
This research is about the accuracy of funds in credit. Indicators related and contextually related to giving, include the principles of moral trust, commercial principles, financial and collateral principles. The research method uses a library research approach. Credit in the general context, bank considerations in channeling funds, targets and objectives in providing credit funds. Credit actually gives and disposes of various funds that were originally collected through various deposits, whether in the form of current accounts, savings or through deposits. The purpose of credit is more simply, aimed at getting benefits in the form of interest as a form of feedback from the process of giving. The distribution of credit funds that are right on target will have a major impact on the development of the economic sector. This is if the credit is given to whom and who actually needs financial support in starting and starting the economy. So when credit funds are given, for example, to movers and activists in the MSME sector if they need these funds in building their business. Accuracy and distribution of funds that are right on target will produce a very significant effect in the context of financial institutions such as banking and the economy in Indonesia.